Energy from Biomass - Comparision of biogas production at ambient temperature and at mesophilic temperature in semicontenous anaerobic digester using vegetable market waste - Dhanalakshmi Sridevi V.; Srinivasan S. V. (Carbon: Science and Technology, 2014)
Studies are conducted in semicontinuous anaerobic reactors of 2 L Capacity with effective volume of 1.5 L. Experiments were carried out in the mesophilic temperature range maintained at 35°C in a thermostat, and parallel experiments were performed at ambient temperature on biogas production from the month of Februray to August. The reactors were operated with an organic loading rate of 0.5 gVS/L/d with 25 days HRT. The feed stock used for the study was vegetable market waste obtained from Koyambedu vegetable market. The specific biogas production was found to be 0.530 L gVS add-1 for the reactor operated at mesophilic temperature and in the range of 0.431 to 0.732 L gVSadd -1 for the reactor operated in the ambient temperature condition from the month of February to August. The daily biogas production was found to be similar (approximately 350 mL/d) when reactors were operated at mesophilic and ambient temperature except for the period of May and June wherein higher amount of daily biogas production (472 and 529 mL/d) was observed in the reactor operated at ambient temperature. The ratio of total VFA and alkalinity and propionic acid to acetic acid (PA/AA) was found to be in the range of 0.25 – 0.4 and 0.34 - 1.38 during the operation of the reactor for the entire period, which was within the range reported for digester stability.